The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.ydbio.2009.05.548
|View full text |Cite
|
Sign up to set email alerts
|

Developmental origins of species-specific muscle pattern

Abstract: Vertebrate jaw muscle anatomy is conspicuously diverse but developmental processes that generate such variation remain relatively obscure. To identify mechanisms that produce species-specific jaw muscle pattern we conducted transplant experiments using Japanese quail and White Pekin duck, which exhibit considerably different jaw morphologies in association with their particular modes of feeding. Previous work indicates that cranial muscle formation requires interactions with adjacent skeletal and muscular conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 129 publications
(155 reference statements)
5
85
0
Order By: Relevance
“…In vertebrates, skeletal muscles which form in the head, trunk and limbs are patterned by extrinsic cues from surrounding tissues to adopt specific arrangements of muscle fibres in the adult form [23][24][25][26][27][28][29][30][31] . For example, somite-derived limb muscle precursor cells migrate into the limb bud which is filled with lateral platederived connective tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In vertebrates, skeletal muscles which form in the head, trunk and limbs are patterned by extrinsic cues from surrounding tissues to adopt specific arrangements of muscle fibres in the adult form [23][24][25][26][27][28][29][30][31] . For example, somite-derived limb muscle precursor cells migrate into the limb bud which is filled with lateral platederived connective tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Neural crest (NC) cells that migrate out of the caudal midbrain and rostral hindbrain are the only source of skeletogenic mesenchyme within the mandibular primordia (Couly et al, 1993;Köntges and Lumsden, 1996;Le LiĂšvre and Douarin, 1975;Noden, 1978;Noden and Schneider, 2006). Previous work has shown that the orchestration of developmental programs regulating jaw size is under the regulatory control of NC Jheon and Schneider, 2009;Schneider, 2005;Schneider and Helms, 2003;Tokita and Schneider, 2009), but how NC achieves this complex task remains unclear.…”
Section: Research Articlementioning
confidence: 99%
“…We previously demonstrated that head muscle patterning and differentiation are governed by the interaction of head muscle progenitors with the adjacent CNC cells (Rinon et al, 2007;Tzahor et al, 2003). Therefore, CNC cells impose anatomical features of the musculoskeletal architecture upon their neighbors (Grenier et al, 2009;Heude et al, 2010;Rinon et al, 2007;Tokita and Schneider, 2009).…”
Section: Introductionmentioning
confidence: 99%